Entrances to analyze the profitability of the customer - an analytical study of the theory - - عزام عبد الوهاب عبد الكريم; نزار حبيب عباس (Iraqi Journal for Administrative Sciences, 2024)
Become a process of analyzing the profitability of the customer and one of the methods useful for business organizations, and through the provision of information extensive and accurate customer as well as specifically for revenues, costs, and profits derived from the customer or group of customers. The decisions concerning the relationship with the customer and one of the important decisions undertaken accomplishing the senior management of the company, and used the analysis of profitability of the customer for the purpose of obtaining information related to it, and thus contribute to this process in the development of decisions on the customer. and head smart companies at the present time is not only about building long term relationships and profitable towards the customer, but would like to having a life, get the value of the life of the customer, make the most of its purchases, and we must look at customers as assets must be managed and to be maximized properly. and decreases the amount of information relating to profit customers in practice to work companies, as designed accounting systems for the analysis of profitability of the product without regard to the customer in most cases, therefore, will address this research for many of the paragraphs relating to the process of analysis of profitability of the customer. The search to three paragraphs, a basic, relating to the first paragraph the methodology of research, which included the problem of research, and its importance, and its objectives. relates to the second paragraph aspect of theoretical research, which included the paragraphs relating to the concept of analysis of profitability of the customer, and analysis of cost, and uses of information resulting from the profitability of the customer, the advantages of the process of analyzing profitability of the customer, and standards (models) profitability of the customer, and finally building relationships with the customer. The third paragraph was included conclusions and recommendations for research.